Design, Synthesis and Biological Evaluation of Neogliptin, a Novel 2-Azabicyclo[2.2.1]heptane-Based Inhibitor of Dipeptidyl Peptidase-4 (DPP-4) - Ivan O. Maslov; Tatiana V. Zinevich; Olga G. Kirichenko; Mikhail V. Trukhan; Sergey V. Shorshnev; Natalya O. Tuaeva; Maxim A. Gureev; Amelia D. Dahlén; Yuri B. Porozov; Helgi B. Schiöth; Vladimir M. Trukhan (MDPI AG, 2022)
Compounds that contain (R)-3-amino-4-(2,4,5-trifluorophenyl)butanoic acid substituted with bicyclic amino moiety (2-aza-bicyclo[2.2.1]heptane) were designed using molecular modelling methods, synthesised, and found to be potent DPP-4 (dipeptidyl peptidase-4) inhibitors. Compound 12a (IC50 = 16.8 ± 2.2 nM), named neogliptin, is a more potent DPP-4 inhibitor than vildagliptin and sitagliptin. Neogliptin interacts with key DPP-4 residues in the active site and has pharmacophore parameters similar to vildagliptin and sitagliptin. It was found to have a low cardiotoxic effect compared to sitagliptin, and it is superior to vildagliptin in terms of ADME properties. Moreover, compound 12a is stable in aqueous solutions due to its low intramolecular cyclisation potential. These findings suggest that compound 12a has unique properties and can act as a template for further type 2 diabetes mellitus drug development.